2014
DOI: 10.1177/0022034513519800
|View full text |Cite
|
Sign up to set email alerts
|

Prosthetic Abutment Height is a Key Factor in Peri-implant Marginal Bone Loss

Abstract: In this study, we analyzed the influence of prosthetic abutment height on marginal bone loss (MBL) around implants in the posterior maxilla. In this retrospective cohort study, the radiographically determined MBL was related to the height of the abutments of internal conical connection implants at 6 and 18 months post-loading. Data were gathered on age, sex, bone substratum, smoking habit, history of periodontitis, and prosthetic features, among other variables. A linear mixed model was used for statistical an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

11
126
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(138 citation statements)
references
References 19 publications
11
126
1
Order By: Relevance
“…The presence of initially thicker crestal mucosa or augmenting thin tissue at the time of placement may attenuate marginal bone changes after implant placement. 18 While the above studies have concluded that thicker PMT, whether it is initially thick or thin and augmented, is preferred, the authors of a recent systematic review have concluded that there is insufficient evidence to establish a minimum tissue thickness that would be required to prevent marginal bone level changes. Sites with initially thin tissue that were not grafted lost a significantly greater amount of bone (1.2 ± 0.08 mm) as compared to the thingrafted and thick groups (0.22 ± 0.06 mm).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of initially thicker crestal mucosa or augmenting thin tissue at the time of placement may attenuate marginal bone changes after implant placement. 18 While the above studies have concluded that thicker PMT, whether it is initially thick or thin and augmented, is preferred, the authors of a recent systematic review have concluded that there is insufficient evidence to establish a minimum tissue thickness that would be required to prevent marginal bone level changes. Sites with initially thin tissue that were not grafted lost a significantly greater amount of bone (1.2 ± 0.08 mm) as compared to the thingrafted and thick groups (0.22 ± 0.06 mm).…”
Section: Discussionmentioning
confidence: 99%
“…For Galindo‐Moreno et al, 25 abutment height is a key factor in MBL, and they reported higher MBL for abutments <2 mm compared with those ≥2 mm. In their study, 315 implants placed in the posterior maxilla in 131 patients with follow‐up of 18 months were included.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, regardless if implants were placed either in the maxilla or mandible, and without specifying supporting tissue (i.e., grafts or native bone), implants still presented good results because only 20% of individuals and 11% of sites lost >1 mm, whereas 8% of individuals and 4% of sites lost >2 mm of marginal bone 24 . Galindo‐Moreno et al 25 , 26 compared MBL between native bone and grafted sinus, resulting in statistically significant differences in MBL between implants placed in grafted (1.09 mm) versus pristine (0.71 mm) bone at the 12‐month follow‐up. However, there were no differences in subsequent progression rate, which is in agreement with a previous study 13 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, through early and late translation stages, we present clinical trials and observational research answering clinical questions, such as how we assess caries activity and prevention (Cagetti et al, 2014;Kuper et al, 2014), implant dentistry (Galindo-Moreno et al, 2014), saliva diagnostics for oral cancer (Momen-Heravi et al, 2014), and cardiovascular diseases (Miller et al, 2014).…”
mentioning
confidence: 99%